Implementasi Smart Green Kids Sebagai Penolah Sampah di SDN Cabe Ilir 3 Pondok Cabe, Tangerang Selatan - Saragih, Nurhayani; Mansur, Suraya; Harahap, Rachmita Maun; Octory, Gadis (Jurnal Abdi Masyarakat (JAM), 2024)
The Smart Child Green Kids program was implemented to educate elementary school students as an effort to reduce the amount of waste. Elementary school students were chosen because it was deemed necessary to provide early education to children as a group that could be formed in an effort to instill values, attitudes and skills in waste management. Households are one of the biggest contributors to waste, especially because the behavior of household members often throws rubbish carelessly or throws rubbish into rivers. The reasons for this include, among other things, people’s lack of understanding about the types of waste and efforts to manage household waste. This Community Service activity aims to strengthen children’s competence in sorting and disposing of waste according to type. The solution offered is to transfer knowledge through workshops in schools.